Extreme heat exposure in pregnancy and risk for preterm birth, low birth weight and stillbirths. (30th September 2020) - Böckmann, M; Chersich, M F; Pham, M D; Areal, A; Haghighi, M M; Manyuchi, A; Swift, C; Wernecke, B; Robinson, M; Hetem, R S
Abstract: Background: Exposure to high ambient temperatures during pregnancy may increase the risk of adverse pregnancy outcomes due to physiological and anatomical changes in pregnancy compromising the ability to thermoregulate. Methods: A systematic review and meta-analysis of studies that assessed associations between ambient heat, and preterm birth, birth weight and stillbirths. Articles were identified through a search of Medline (PubMed) and Web of Science. Titles and abstracts were screened, eligible studies extracted and risk of bias assessed using the Joanna Briggs Institute appraisal tools. Results: 14, 880 records were screened and a total of 70 studies included. In 40 of 47 studies, preterm births were more frequent at higher than lower temperatures. In random effects meta-analysis, the odds of a preterm birth rose 1.05-fold per 1 °C increase in temperature (95%CI=1.03, 1.07), and 1.16 fold during heat waves (95%CI=1.10, 1.23). Reduced birth weight associated with higher temperature was found in in 18 of 28 studies, with considerable heterogeneity. Studies on stillbirths (n = 8) all showed temperature-stillbirth associations, with stillbirths increasing 1.05-fold per 1 °C rise in temperature (95%CI=1.01, 1.08). Associations between temperature and outcomes were largest among women in lower socioeconomic groups and at age extremes. The multiple temperature metrics and lag analyses limited comparison between studies and settings. Conclusions: As frequency of heat exposures is increasing, prevention for pregnant women during heat waves should become a standard aspect of heat adaptation. Key messages: Increase in extreme temperature events may have major implications for child health unless much more is done to provide heat adaptation services for pregnant women. Links between socio-economic status and study outcomes suggest higher vulnerability for already disadvantaged groups.